Novel photochromic piezoelectric ceramic and preparation method thereof
Through copper-doped potassium sodium niobate-based high-entropy ceramic materials, the high cost and environmental pollution caused by rare earth element dependence are solved, and high-performance visible light photochromic ceramics are achieved, with good cycle stability and optical performance. , suitable for the low-carbon and sustainable development of the optoelectronic ceramics industry.
Patent Information
- Application Number
- CN202411316137.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2024-12-13
AI Technical Summary
Existing photochromic ceramic materials driven by visible light mainly rely on rare earth elements, resulting in high costs, serious environmental pollution, poor fatigue resistance and reversibility, making it difficult to meet the low-carbon and sustainable development needs of the photoelectric ceramic industry.
Using copper oxide-doped potassium sodium niobate-based high-entropy ceramic material, the reversible photochromic reaction from green to dark brown through alternating light and thermal stimulation, avoiding the use of rare earth elements, and optimizing the content of copper oxide to improve the Cyclic stability and optical properties of the material.
A photochromic ceramic material without rare earth elements is realized, with excellent visible photochromic properties, fluorescent luminescence characteristics and piezoelectric response properties, significantly improving the environmental and economic benefits of the material, and the luminescence modulation contrast after multiple cycles Basically unchanged, suitable for optical data storage applications.
Smart Images

Figure CN119118665A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of dielectric ceramic materials, and in particular relates to a novel photochromic piezoelectric ceramic and a preparation method thereof. Background Art
[0002] Inorganic photochromic materials can undergo reversible color changes under light, have excellent thermal stability, chemical resistance and mechanical strength, and have broad application prospects in optoelectronic devices, optical data storage and optical switches. However, traditional inorganic photochromic materials are mainly sensitive to ultraviolet rays and have limited response to visible light wavelengths, resulting in poor fatigue resistance, unstable reversibility and long response time. In contrast, visible light-driven photochromic materials are able to make more full use of solar energy and have rich excitation laser light sources. They have great potential value in applications such as smart windows, optical data storage, sensors, etc., and have become a research hotspot in the field of materials science.
[0003] Currently, visible light-driven photochromic ceramics are mainly obtained by doping with rare earth elements. For example, Zhang et al. reported that Er 3+ / Pr 3+ - Co-doped K 0.5 Na 0.5 NbO3 ceramics exhibit tunable luminescence and have a luminescence modulation contrast as high as 74.52%. Jia et al. prepared Tb-doped NbO3 ceramics by conventional solid-state techniques. 3+ K 0.5 Na 0.5 NbO3 ceramics have achieved luminescence modulation and light transmittance control based on the photochromic effect. In addition, Ba / Sm co-doped K 0.5 Na 0.5 Photochromic behavior has also been observed in NbO3 transparent ceramics; Patent document CN110372378A also mentions the preparation method of europium / barium strontium titanate modified ceramic color change. However, although rare earth elements play a key role in luminescence research, their mineral production is small, expensive, and the mining process causes serious environmental pollution.
[0004] Therefore, the development of high-performance rare earth element-free photochromic ceramics is crucial for the low-carbon sustainable development of the optoelectronic ceramic industry. In view of this, the present invention is proposed. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a new photochromic piezoelectric ceramic and a preparation method thereof. The prepared ceramic material does not contain rare earth elements, has low cost, and at the same time has excellent visible light photochromic properties, fluorescent luminescence properties and piezoelectric response properties.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing a novel photochromic piezoelectric ceramic, comprising the following steps:
[0008] S1. Weighing: According to the chemical stoichiometric formula [(K 0.43 Na 0.57 ) 0.94 Li 0.06 ][(Nb 0.94 Sb 0.06 ) 0.95 Ta 0.05 ]O3+xmol%CuO Weigh the precursor materials of potassium salt, sodium salt, lithium salt, niobium salt, antimony salt, tantalum salt and copper oxide respectively and set aside; wherein, 0≤x≤3.5;
[0009] S2, primary ball milling: mixing the precursor raw materials weighed in step S1 and then ball milling;
[0010] S3, pre-calcining: pre-calcining the slurry after ball milling in step S2;
[0011] S4, secondary ball milling: ball milling the raw material pre-fired in step S3 again, and drying to obtain pre-fired ceramic powder;
[0012] S5, molding: adding a binder to the pre-fired ceramic powder obtained in step S4, and then pressing and molding to obtain a ceramic embryo;
[0013] S6, debinding and sintering: the ceramic body obtained in step S5 is heated and then subjected to heat preservation treatment to obtain a debinding green body; then the debinding green body is sintered to obtain a photochromic piezoelectric ceramic.
[0014] As a preferred embodiment of the technical solution of the present invention, in step S1, the precursor raw materials of potassium salt, sodium salt, lithium salt, niobium salt, antimony salt and tantalum salt are K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3 and Ta2O5 respectively.
[0015] As a preferred embodiment of the technical solution of the present invention, in step S2, zirconium dioxide ball milling is used for ball milling, and 70-90% of the total mass of the precursor raw materials is added with anhydrous ethanol before ball milling; the ball milling time is 0.5-5h.
[0016] As a preferred embodiment of the technical solution of the present invention, in step S3, the pre-firing temperature is 820-880° C., and the pre-firing time is 0.5-5 h.
[0017] As a preferred embodiment of the technical solution of the present invention, in step S4, the secondary ball milling time is 3 to 8 hours.
[0018] As a preferred embodiment of the technical solution of the present invention, in step S5, the binder is a 5-10wt% polyvinyl alcohol ethanol solution.
[0019] As a preferred embodiment of the technical solution of the present invention, in step S5, the pressing pressure is 2 to 4 MPa; and the pressing time is 10 to 20 s.
[0020] As a preferred embodiment of the technical solution of the present invention, in step S6, the insulation treatment temperature is 600-700° C., and the insulation treatment time is 0.5-5 h.
[0021] As a preferred embodiment of the technical solution of the present invention, in step S6, the sintering temperature is 1000-1100° C., and the sintering time is 2-8 hours.
[0022] In a second aspect, the present invention aims to protect the photochromic piezoelectric ceramics prepared by the above method.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The preferred matrix elements of the present invention are determined by screening [(K 0.43 Na 0.57 ) 0.94 Li 0.06 ][(Nb 0.94 Sb 0.06 ) 0.95 Ta 0.05 ]O3 (i.e. KNLNST) is used as the matrix material and is treated with doped or undoped CuO, and the development of potassium sodium niobate-based photochromic piezoelectric ceramics without rare earth elements is successfully realized.
[0025] (2) The present invention optimizes the content of copper oxide and achieves a reversible photochromic reaction from green to dark brown by alternating light and heat stimulation of KNLNST-0.3CuO ceramics. The luminescence modulation contrast under 407nm irradiation is as high as 44.6%, and the luminescence modulation contrast remains basically unchanged after multiple cycles, showing good cycle stability. In addition, the optical information write-erase test further demonstrates its feasibility for optical data storage applications.
[0026] (3) The present invention has significant environmental and economic benefits. Compared with the rare earth element doping strategy, the present invention adopts the copper oxide doping strategy to induce oxygen vacancies, without the use of expensive rare earth elements, and only uses cheap and readily available potassium, sodium, lithium, niobium, antimony and tantalum metal elements, which significantly improves the environmental and economic benefits of the photochromic ceramic material from elements to materials in the entire cycle. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 is the XRD pattern of KNLNST-xCuO ceramics;
[0028] Figure 2 The piezoelectric properties of KNLNST-xCuO ceramics;
[0029] Figure 3 Reversible optical data writing and erasing of KNLNST-xCuO ceramics;
[0030] Figure 4 is the fluorescence spectrum of KNLNST-xCuO ceramics;
[0031] Figure 5 is the luminescence modulation contrast of KNLNST-xCuO ceramics;
[0032] Figure 6 Photochromic cycling stability of KNLNST-0.3CuO ceramics. DETAILED DESCRIPTION
[0033] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The present invention provides a potassium sodium niobate-based high entropy ceramic matrix material, the stoichiometric formula of which is [(K 0.43 Na 0.57 ) 0.94 Li 0.06 ][(Nb 0.94 Sb 0.06 ) 0.95 Ta 0.05 ]O3, the embodiment of the present invention is abbreviated as KNLNST. Based on the mulberry matrix material, by copper oxide doping, the photochromic piezoelectric ceramic material obtained by the present invention not only does not contain rare earth elements and has low cost, but also has excellent visible light photochromic performance, fluorescent luminescence characteristics and piezoelectric response performance. Among them, the copper oxide doped ceramic is abbreviated as KNLNST-xCuO (x is the molar percentage of CuO).
[0035] For the above-mentioned doped modified ceramic, the present invention provides a preparation method, comprising the following steps:
[0036] S1. Weighing: According to the chemical stoichiometric formula [(K 0.43 Na 0.57 ) 0.94 Li 0.06 ][(Nb 0.94 Sb 0.06 ) 0.95Ta 0.05 ]O3+xmol%CuO Weigh the precursor materials of potassium salt, sodium salt, lithium salt, niobium salt, antimony salt, tantalum salt and copper oxide respectively and set aside; wherein, 0≤x≤3.5;
[0037] S2, primary ball milling: mixing the precursor raw materials weighed in step S1 and then ball milling;
[0038] S3, pre-calcining: pre-calcining the slurry after ball milling in step S2;
[0039] S4, secondary ball milling: ball milling the raw material pre-fired in step S3 again, and drying to obtain pre-fired ceramic powder;
[0040] S5, molding: adding a binder to the pre-fired ceramic powder obtained in step S4, and then pressing and molding to obtain a ceramic embryo;
[0041] S6, debinding and sintering: the ceramic body obtained in step S5 is heated and then subjected to heat preservation treatment to obtain a debinding green body; then the debinding green body is sintered to obtain a photochromic piezoelectric ceramic.
[0042] In the above technical solution, based on the ceramic matrix material [(K 0.43 Na 0.57 ) 0.94 Li 0.06 ][(Nb 0.94 Sb 0.06 ) 0.95 Ta 0.05 ]O3, and treating it with undoped / doped CuO can obtain photochromic piezoelectric ceramic materials with excellent performance. The method is simple, does not involve the use of rare earth elements, and has controllable costs.
[0043] In some embodiments, in step S1, the precursor raw materials of potassium salt, sodium salt, lithium salt, niobium salt, antimony salt and tantalum salt are K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3 and Ta2O5 respectively. More preferably, the purity of the above raw materials is: K2CO 3, Purity ≥99.98%; Na2CO3, purity ≥99.90%; Li2CO3, purity ≥99.99%; Nb2O5, purity ≥99.99%; Sb2O3, purity ≥99.99%; Ta2O5, purity ≥99.99%; CuO, purity ≥99.90%.
[0044] In some embodiments, in step S2, the ball milling is performed by a zirconium dioxide ball mill, and 70-90% of the total mass of each precursor raw material is added with anhydrous ethanol before the ball milling; the ball milling time is 0.5-5 hours. Preferably, the amount of anhydrous ethanol added is 80% of the total mass of each precursor raw material, and the ball milling time is 4 hours.
[0045] In some embodiments, in step S3, the pre-burning temperature is 820-880°C, and the pre-burning time is 0.5-5h. It is understandable that the pre-burning temperature can be a value among 820°C, 825°C, 830°C, 835°C, 840°C, 845°C, 850°C, 855°C, 860°C, 865°C, 870°C, 875°C, 880°C, or any value within the above range; similarly, the pre-burning time can be a value among 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or any value within the above range; preferably, the pre-burning time is 3h.
[0046] In some embodiments, in step S4, the secondary ball milling time is 3 to 8 hours. The ball milling also uses a zirconium dioxide ball mill, and the ball milling time can be a value among 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, 8 hours or any value within the above range. Preferably, the ball milling time is 4 hours. The drying temperature is preferably 100°C.
[0047] In some embodiments, in step S5, the binder is a 5-10 wt % polyvinyl alcohol ethanol solution; more preferably, the concentration of the binder is 8 wt %.
[0048] In some embodiments, in step S5, the pressing pressure is 2-4 MPa; the pressing time is 10-20 s. It is understood that the pressing pressure can be 2 MPa, 2.1 MPa, 2.2 MPa, 2.3 MPa, 2.4 MPa, 2.5 MPa, 2.6 MPa, 2.7 MPa, 2.8 MPa, 2.9 MPa, 3 MPa, 3.1 MPa, 3.2 MPa, 3.3 MPa, 3.4 MPa, 3.5 MPa, 3.6 MPa, 3.7 MPa, 3.8 MPa, 3.9 MPa, 4 MPa or any value within the above range; the pressing time can be 10 s, 11 s, 12 s, 13 s, 14 s, 15 s, 16 s, 17 s, 18 s, 19 s, 20 s or any value within the above range. Preferably, the pressing pressure is 3 MPa; the pressing time is 15 s.
[0049] In some embodiments, in step S6, the heat preservation treatment temperature is 600-700°C, and the heat preservation treatment time is 0.5-5h. It is understandable that the heat preservation treatment temperature can be a value among 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, 660°C, 670°C, 680°C, 690°C, 700°C, or any value within the above range; the heat preservation treatment time is a value among 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, or any value within the above range. Preferably, the heat preservation treatment temperature is 650°C, and the heat preservation treatment time is 1h.
[0050] In some embodiments, in step S6, the sintering temperature is 1000-1100°C, and the sintering time is 2-8h. It is understood that the sintering temperature can be a value among 1000°C, 1010°C, 1020°C, 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, or any value within the above range; the sintering time can be a value among 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, or any value within the above range. More preferably, the sintering time is 4h.
[0051] Next, the technical solution of the present invention is further described with specific embodiments.
[0052] Example 1
[0053] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0054] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, and Ta2O5;
[0055] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0056] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 880°C for 3 hours.
[0057] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0058] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0059] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1100°C and a sintering holding time of 4 hours to finally obtain KNLNST high entropy ceramics.
[0060] In this embodiment, CuO is not used for doping modification.
[0061] Example 2
[0062] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0063] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, Ta2O5, and weigh 0.1 mol% of CuO;
[0064] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0065] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 880°C for 3 hours.
[0066] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0067] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0068] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1100°C and a sintering holding time of 4 hours to finally obtain a new type of photochromic piezoelectric ceramic.
[0069] Example 3
[0070] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0071] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, Ta2O5, and weigh 0.2 mol% of CuO;
[0072] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0073] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 880°C for 3 hours.
[0074] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0075] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0076] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1100°C and a sintering holding time of 4 hours to finally obtain a new type of photochromic piezoelectric ceramic.
[0077] Example 4
[0078] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0079] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, Ta2O5, and weigh 0.3 mol% of CuO;
[0080] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0081] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 880°C for 3 hours.
[0082] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0083] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0084] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1100°C and a sintering holding time of 4 hours to finally obtain a new type of photochromic piezoelectric ceramic.
[0085] Example 5
[0086] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0087] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, Ta2O5, and weigh 0.5 mol% of CuO;
[0088] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0089] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 880°C for 3 hours.
[0090] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0091] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0092] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1100°C and a sintering holding time of 4 hours to finally obtain a new type of photochromic piezoelectric ceramic.
[0093] Example 6
[0094] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0095] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, Ta2O5, and weigh 0.8 mol% of CuO;
[0096] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0097] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 860°C for 3 hours.
[0098] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0099] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0100] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C, and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1080°C and a sintering holding time of 4 hours, and finally a new type of photochromic piezoelectric ceramic is obtained.
[0101] Example 7
[0102] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0103] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, Ta2O5, and weigh 1.2 mol% of CuO;
[0104] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0105] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 860°C for 3 hours.
[0106] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0107] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0108] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C, and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1080°C and a sintering holding time of 4 hours, and finally a new type of photochromic piezoelectric ceramic is obtained.
[0109] Example 8
[0110] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0111] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, Ta2O5, and weigh 1.5 mol% of CuO;
[0112] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0113] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 860°C for 3 hours.
[0114] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0115] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0116] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C, and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1080°C and a sintering holding time of 4 hours, and finally a new type of photochromic piezoelectric ceramic is obtained.
[0117] Example 9
[0118] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0119] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, Ta2O5, and weigh 2 mol% of CuO;
[0120] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0121] (3) Pre-calcination: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-calcination at a temperature of 840°C for 3 hours.
[0122] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0123] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0124] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C, and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1040°C and a sintering holding time of 4 hours, and finally a new type of photochromic piezoelectric ceramic is obtained.
[0125] Example 10
[0126] A method for preparing a novel photochromic piezoelectric ceramic comprises the following steps:
[0127] (1) Weighing: According to the stoichiometric ratio of each component in the chemical formula KNLNST, weigh the metal precursor compound raw materials, including K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3, Ta2O5, and weigh 3 mol% of CuO;
[0128] (2) Primary ball milling: The weighed precursor material and zirconium dioxide ball milling beads were placed in a ball milling jar, and 80% of the total weight of the drug was added with anhydrous ethanol for ball milling. The speed was increased to 50, 100, 150, 200 and finally 250 r / min every 5 minutes, and finally the ball milling was carried out at a speed of 250 r / min for 4 h;
[0129] (3) Pre-burning: The ground slurry is placed in a constant temperature drying oven at 100°C to completely evaporate the alcohol in the drug, then placed in a crucible and transferred to a muffle furnace for pre-burning at a temperature of 820°C for 3 hours.
[0130] (4) Secondary ball milling: The pre-fired powder is mixed with anhydrous ethanol and ball milled for 4 h, and the ball-milled slurry is dried at 100 °C to obtain the final pre-fired ceramic powder;
[0131] (5) Molding: Add a binder to an appropriate amount of pre-fired ceramic powder and mix them evenly by grinding in a mortar. Fill a mold with the mixed powder and press it into shape using a tablet press. The applied pressure is 3 MPa and the pressure is kept constant for 15 seconds to obtain a ceramic green disc with a flat and fine surface and no internal stratification. The diameter is about 12 mm and the thickness is about 1 mm.
[0132] (6) Debinding and sintering: The pressed ceramic body is placed in a muffle furnace and heated to 650°C and kept warm for 1 hour for debinding. The debinded green body is placed in a muffle furnace for sintering at a sintering temperature of 1000°C and a sintering holding time of 4 hours to finally obtain a new type of photochromic piezoelectric ceramic.
[0133] The performance of the ceramic materials prepared in each example was tested. Figure 1 to Figure 6 .
[0134] from Figure 1It can be seen that all ceramic samples exhibit a perovskite phase structure, and the ratio of the peak areas of (220) and (002) diffraction increases with the increase in the content of copper oxide. When x < 0.5, the samples are mainly tetragonal perovskite crystal phases; when x > 1.2, the samples are mainly orthorhombic perovskite phases; when 0.5 < x < 1.2, the tetragonal perovskite phase and the orthorhombic perovskite phase coexist.
[0135] It can be seen from Figure 2 that as the content of copper oxide (CuO) increases from 0 to 3.0 mol%, d33 (piezoelectric strain constant) and kp (electromechanical coupling coefficient) show a downward trend, decreasing from 277 pC / N and 45.6% to 129 pC / N and 29.7% respectively; while Qm (mechanical quality factor) continuously increases and reaches a maximum value of 302 when x = 3.0 mol%, which is almost six times that of pure KNLNST ceramics.
[0136] It can be seen from Figure 3 that as the value of x increases, the color of the untreated KNLNST-xCuO ceramics gradually changes from light yellow to dark green and finally to black, indicating that the higher the content of copper oxide, the stronger the absorption of the whole visible spectrum by the ceramics. After irradiation with light of 407 nm wavelength, an obvious color change of the ceramics can be observed; then after heat treatment at 200 °C, the color of the ceramics quickly returns to the original color.
[0137] It can be seen from Figure 4 that under excitation at 375 nm, significant fluorescence characteristic peaks appear in the ceramic samples, located near 400 nm and 560 nm respectively, and the intensity of the fluorescence peaks gradually decreases with the increase in the content of copper oxide.
[0138] It can be seen from Figure 5 that as the content of copper oxide increases, the photoluminescence modulation contrast first increases and then decreases, and when x is 0.3, the maximum photoluminescence modulation contrast is 44.6%.
[0139] It can be seen from Figure 6 that when x is 0.3, the photoluminescence modulation contrast of the ceramic samples remains stable during 8 coloration and decoloration cycles, indicating that the samples have good cycle stability.
[0140] The technical concept of the present invention is illustrated by the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement to the present invention, the equivalent replacement of individual raw materials of the products of the present invention, the addition of auxiliary components, the selection of specific methods, etc., all fall within the protection scope and the disclosure scope of the present invention.
Claims
1. A method for preparing a novel photochromic piezoelectric ceramic, characterized in that: The steps include: S1. Weighing: According to the chemical stoichiometric formula [(K 0.43 Na 0.57 ) 0.94 Li 0.06 ][(Nb 0.94 Sb 0.06 ) 0.95 Ta 0.05 ]O3+x mol%CuO Weigh the precursor materials of potassium salt, sodium salt, lithium salt, niobium salt, antimony salt, tantalum salt and copper oxide respectively and set aside; wherein, 0≤x≤3.5; S2, primary ball milling: mixing the precursor raw materials weighed in step S1 and then ball milling; S3, pre-calcining: pre-calcining the slurry after ball milling in step S2; S4, secondary ball milling: ball milling the raw material pre-fired in step S3 again, and drying to obtain pre-fired ceramic powder; S5, molding: adding a binder to the pre-fired ceramic powder obtained in step S4, and then pressing and molding to obtain a ceramic embryo; S6, debinding and sintering: the ceramic body obtained in step S5 is heated and then subjected to heat preservation treatment to obtain a debinding green body; then the debinding green body is sintered to obtain a photochromic piezoelectric ceramic.
2. The method for preparing a novel photochromic piezoelectric ceramic according to claim 1, characterized in that: In step S1, the precursor raw materials of potassium salt, sodium salt, lithium salt, niobium salt, antimony salt and tantalum salt are K2CO3, Na2CO3, Li2CO3, Nb2O5, Sb2O3 and Ta2O5 respectively.
3. The method for preparing a novel photochromic piezoelectric ceramic according to claim 1, characterized in that: In step S2, zirconium dioxide ball milling is used for ball milling, and 70-90% of the total mass of the precursor raw materials is added with anhydrous ethanol before ball milling; the ball milling time is 0.5-5h.
4. The method for preparing a novel photochromic piezoelectric ceramic according to claim 1, characterized in that: In step S3, the pre-firing temperature is 820-880° C., and the pre-firing time is 0.5-5 h.
5. The method for preparing a novel photochromic piezoelectric ceramic according to claim 1, characterized in that: In step S4, the secondary ball milling time is 3 to 8 hours.
6. The method for preparing a novel photochromic piezoelectric ceramic according to claim 1, characterized in that: In step S5, the binder is a 5-10 wt % polyvinyl alcohol ethanol solution.
7. The method for preparing a novel photochromic piezoelectric ceramic according to claim 1, characterized in that: In step S5, the pressing pressure is 2-4 MPa, and the pressing time is 10-20 s.
8. The method for preparing a novel photochromic piezoelectric ceramic according to claim 1, characterized in that: In step S6, the heat preservation treatment temperature is 600-700° C., and the heat preservation treatment time is 0.5-5 h.
9. The method for preparing a novel photochromic piezoelectric ceramic according to claim 1, characterized in that: In step S6, the sintering temperature is 1000-1100° C., and the sintering time is 2-8 hours.
10. A photochromic piezoelectric ceramic prepared by the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Piezoelectric ceramic, method for producing same, and piezoelectric device
CN102395539A
High-mechanical-strength potassium-sodium niobate based lead-free piezoelectric ceramic material, preparation method of material and application of material
CN107382318A
Potassium-sodium niobate-based lead-free piezoelectric ceramic material with ultralow dielectric loss and preparation method thereof
CN113563075A
Low-temperature sintered potassium-sodium niobate-based lead-free piezoelectric ceramic material and preparation method thereof
CN113582692A
Electro-optic ceramic materials
US20150376068A1
